The Role of Family in Legitimizing Early Marriage In Central Lombok District: A Perspective Islamic Family Law - Maulana, Muhammad Gazi Firman (JURNAL PENELITIAN KEISLAMAN, 2025)
The phenomenon of early marriage is still rampant in various parts of Indonesia, including Central Lombok District, West Nusa Tenggara, which recorded the second highest number of cases in the province. In many cases, the family not only gives its blessing, but becomes the main actor in the decision-making of early marriage, for reasons of maintaining honor, reducing the economic burden, or continuing traditions such as merariq. This study uses netnography research with a descriptive-analytical approach through literature study with Berger and Luckmann's social construction theory analysis. The results of the analysis show that the family acts as a social construction agent that legitimizes early marriage as a social reality that is considered normal, even ideal. This reality ultimately weakens the normative function of marriage law, because the social values formed by families are often stronger than formal state regulations.